What drives adoption intention of electric vehicles in India? An integrated UTAUT model with environmental concerns, perceived risk and government support. (March 2022) - Jain, Nikunj Kumar; Bhaskar, Kalyan; Jain, Sourabh
Abstract: The purpose of this study is to explore the factors that affect adoption intention of electric vehicles (EVs) in India. An integrated model using Unified Theory of Acceptance and Use of Technology (UTAUT) was developed to forecast customer's adoption intention towards EVs in India using perceived risk as the predictor and environmental concerns and government support as the moderators. Quantitative data from 284 customers was analyzed using hierarchical linear regression analysis and verified with necessary conditions analysis. The findings show that performance expectancy and facilitating conditions positively affect adoption intention of EVs, whereas perceived risk negatively affects adoption intention of EVs. Government support was found to moderate the relationship between perceived risk and adoption intention such that it reduces the inverse relationship of perceived risk on adoption intention. The results validate UTAUT by studying it in the context of EV's adoption in India and adds to the literature on psychological traits affecting adoption intention of new products. Implications from results for policy and practice in terms of specific measures that could be taken by automobile firms and governments to promote adoption based on results are also discussed.